Space Function and Shape of Balai Adat in Koto Sentajo Traditional Village - Sepli Yandri; Suzanna Ratih Sari; Agung Budi Sardjono (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2019)
Abstract. The country of Indonesia is known for its diversity of tribes in various regions. One area that still has traditional villages is the Koto Sentajo area. the lives of people in the Koto Sentajo village still use traditional values that are inherited from generation to generation. As a village, it certainly has a shelter in the form of a house and a worship facility in the form of a mosque. In the Koto Sentajo traditional village, there are traditional buildings called Balai adat. The existence of a Balai adat is inseparable from the traditional values that develop in the community. Balai adat has an important role in a traditional village as a gathering place and deliberation to find solutions to problems that occur in the village. The purpose of this study was to find out the role of Balai adat in koto sentajo village and to conclude the function of space and the shape of the building that became the identity of traditional settlements in Kuantan Singingi. The method of descriptive analysis is used as a way of delivering in-depth descriptions that will discuss in depth how the functions of space and the forms contained in the traditional hall in Koto Sentajo. Keywords: Balai Adat, Koto Sentajo, Kuantan Singingi.